2020
DOI: 10.1021/jacs.9b12457
|View full text |Cite
|
Sign up to set email alerts
|

A Selenourea-Thiourea Brønsted Acid Catalyst Facilitates Asymmetric Conjugate Additions of Amines to α,β-Unsaturated Esters

Abstract: β-Amino esters are obtained with high levels of enantioselectivity via the conjugate addition of cyclic amines to unactivated α,β-unsaturated esters. A related strategy enables the kinetic resolution of racemic cyclic 2-arylamines, using benzyl acrylate as the resolving agent. Reactions are facilitated by an unprecedented selenourea-thiourea organocatalyst. As elucidated by DFT calculations and 13 C kinetic isotope effect studies, the ratelimiting and enantiodetermining step of the reaction is the protonation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 83 publications
0
40
0
Order By: Relevance
“…The catalyst used acts as an H-bond catalyst (Scheme 9). [15] Scheme 1. (A) CÀ N bond formation reaction in a biological system for the biosynthesis of retronecine.…”
Section: Aza-michael Reactionmentioning
confidence: 99%
“…The catalyst used acts as an H-bond catalyst (Scheme 9). [15] Scheme 1. (A) CÀ N bond formation reaction in a biological system for the biosynthesis of retronecine.…”
Section: Aza-michael Reactionmentioning
confidence: 99%
“…[14,17,31,32] Recently, a few cases reported that thioureas can also act as Brønsted acids in a catalytic fashion. [33,34] In general, electron-poor aryl moieties adjacent to the thiourea nitrogen enhance the hydrogen donor ability and thus the catalytic activity. [2,35] Most often, 3,5-bis(trifluorometh-yl) phenyl [35] or other fluoro substituted aryl moieties [1,2,19,34,36] are used at one or both sites of the thiourea group for this task.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] In general, electron-poor aryl moieties adjacent to the thiourea nitrogen enhance the hydrogen donor ability and thus the catalytic activity. [2,35] Most often, 3,5-bis(trifluorometh-yl) phenyl [35] or other fluoro substituted aryl moieties [1,2,19,34,36] are used at one or both sites of the thiourea group for this task. Nevertheless, several moieties have been reported that also lead to a significant increase of the catalytic activity of thioureas using electron-withdrawing groups, such as aromatic acetyl or sulfone [37,38] as well as sulfoxide moieties, [10] directly attached to the thiourea group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations